Analisis Kinerja Keuangan Pada Lembaga Perkreditan Desa (LPD) Desa Adat Blahkiuh Kabupaten Badung - HANDAYANI, NI MADE DWI; USTRIYANA, I NYOMAN GEDE; DEWI, NI LUH PRIMA KEMALA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.11, No.1, Juli 2022, 2022)
Financial Performance Analysis at the Village Credit Institution (LPD) of Blahkiuh Traditional Village Badung Regency.  LPD is one of the policies of the Bali Regional Government in an effort to channel capital assistance to rural communities in Bali. The purpose of establishing the LPD is to support the smooth development of the village economy, especially for farmers and small entrepreneurs. By looking at the financial program, especially the balance sheet and income statement, it can be seen the financial condition of the LPD concerned. The ability to grow public trust in the LPD can be done by showing the financial performance of the LPD, where financial performance is carried out to see how far a company has implemented using the rules of financial implementation properly and correctly. Financial performance analysis is very useful for related parties, including: traditional village owners, managers, customers (borrowers and depositors). This study aims to determine the analysis of the financial performance of the Blahkiuh Traditional Village LPD in 2016-2020. The data analysis method used is a quantitative method using the calculation of financial ratio analysis. The results of this study indicate that the financial performance of the Blahkiuh Traditional Village LPD based on the liquidity ratio as measured by the LDR ratio is categorized as healthy, the profitability ratio as measured by the ROA ratio is categorized as healthy, the BOPO ratio is categorized as quite healthy, the ratio of earning assets as measured by the KAP ratio is categorized as healthy and the CPRR ratio is categorized as quite healthy.